STATE TREASURY SPECIAL PURPOSE ENTITIES FOR ORGANISATION OF UEFA EURO 2012 - Marta WIATEREK (Management Systems in Production Engineering, 2012)
Under the provisions of the Act to prepare for UEFA Euro 2012, two State Treasury special purpose entities were formed: PL 2012 Ltd. and National Sports Centre Ltd. PL 2012 company fulfils the primary role in the organization of preparations for UEFA Euro tournament because it was formed for the purposes of the coordination and supervision of the preparatory actions.